PEMILIHAN TIPE GRADASI YANG TAHAN DEFORMASI PLASTIS PADA CAMPURAN BETON ASPAL - Nono Nono (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Flexible pavement defect which is frequently occurred in some regions that have high temperature and heavy loaded traffic is called plastic deformation. There are two factors contributed significantly to plastic deformation in asphalt mixture, they are volumetric of mixture and the use of grade asphalt. Problem in volumetric of mixture can be overcome by choosing appropriate gradation of aggregate that have sufficient void to accommodate asphalt under densification by traffic. To solve the above problem, research on the selection of aggregate gradation as an alternative to anticipate plastic deformation in laboratory scale has been conducted. The result indicated that properties of asphalt mixtures with aggregate gradation cut across Fuller Curve (below restriction zone) is not sensitive to plastic deformation.